EXPLORING THE DIMENSIONS OF COUNTRY OF ORIGIN AND ITS LEVERAGE ON CONSUMER BUYING PREFERENCES: A QUALITATIVE STUDY OF PAKISTANI CONSUMER MARKET (Singaporean Journal of Business Economics and Management, 2015)
This research paper aims to explore and enhance the understanding about the country of origin and its leveraging effect on consumer buying preferences. Firms all around the world consider expanding their businesses into foreign markets. Through reduction in trade barriers and perfections in communication, the dream of becoming a “Global Company” seems relatively easy. Branding with relevant differentiation and value proposition is considered a sound methodology to create patron loyalty across the world. However, the customer’s brand assessment procedure is a complex phenomenon with a sum of factors. One crucial, albeit often ignored, factor is the Country of Origin (COO) of the brand. This paper attempts to explore that how the consumer buying preferences are being affected due to the product’s origin, or “made in” tag. It is an exploratory study, which tries to analyze in detail, through structured interview method, that what kind of impact COO has over customer preference, in which product categories this influence is high and what factors have a potential negative impact on purchase decision. For firms viewing the world as their market, prerequisite for marketers is to realize the consequences of COO effects on their brands and establish policies to counter / control (as the case may be) the influence of COO on its brand. This qualitative research also considers and reviews the effect of COO on brand assessments through the study of backgrounds available in current management literature. It also focuses on the aspects that affect the degree of impact of the COO on the brand. Finally, this study paves the path for the strategists to take advantage of the findings and consider COO image as professed by the customer. This study led to endorsements on how to grab the COO effect for Multinational and Local (Pakistani) firms who intended to enlarge to foreign markets.